2020
DOI: 10.1371/journal.pone.0243541
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of a well-established skill is resistant to distraction: Evidence from an implicit probabilistic sequence learning task

Abstract: The characteristics of acquiring new sequence information under dual-task situations have been extensively studied. A concurrent task has often been found to affect performance. In real life, however, we mostly perform a secondary task when the primary task is already well acquired. The effect of a secondary task on the ability to retrieve well-established sequence representations remains elusive. The present study investigates whether accessing well-acquired probabilistic sequence knowledge is affected by a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…This conclusion is in accordance with the findings that statistical knowledge persists and remains resistant to interference even after 1 year ( Kóbor et al. 2017 ), is intact in dual-task conditions ( Vékony et al. 2019 ) or in certain disorders characterized by cognitive dysfunctions, such as obstructive sleep apnea ( Nemeth et al.…”
Section: Discussionsupporting
confidence: 90%
“…This conclusion is in accordance with the findings that statistical knowledge persists and remains resistant to interference even after 1 year ( Kóbor et al. 2017 ), is intact in dual-task conditions ( Vékony et al. 2019 ) or in certain disorders characterized by cognitive dysfunctions, such as obstructive sleep apnea ( Nemeth et al.…”
Section: Discussionsupporting
confidence: 90%
“…However, given that at least some of the judgement knowledge was unconscious, we can infer some structural knowledge was too (see Fu et al, 2010). Vékony et al (2020) showed an ASRT task (Alternating Serial Reaction Time task in which every other trial is random) was resistant to a secondary task (counting stimuli) at testing, with evidence of above chance exclusion performance -consistent with the application of unconscious structural knowledge being resistant to effects of diminished executive capacity.…”
Section: Conscious Versus Unconscious Learningmentioning
confidence: 83%
“…Serial reaction time tasks of various sorts have been extensively used to assess whether sequence learning can be implicit [1]; developmentally invariant or even superior in children compared to adults [42]; impaired [43], intact [44, 45] or even enhanced [46] in neurological and psychiatric conditions; persistent for months [32] and resistant to distraction [12] even after brief learning; (in)dependent on sleep [33, 47] and subjective sleep quality [48], etc. It would be possible to use the parameterization afforded by models such as the HCRP to ask what components differ significantly between conditions or populations.…”
Section: Discussionmentioning
confidence: 99%